Three levels of regulation lead to protamine and Mst77F expression in Drosophila - Barckmann, Bridlin (2013)
Differentiation from a haploid round spermatid to a highly streamlined, motile sperm requires temporal and spatial regulation of the expression of numerous proteins. One form of regulation is the storage of translationally repressed mRNAs. In Drosophila spermatocytes, the transcription of many of these translationally delayed mRNAs during spermiogenesis is in turn directly or indirectly regulated by testis-specific homologs of TATA-box-binding-protein-associated factors (tTAFs). Here we present evidence that expression of Mst77F, which is a specialized linker histone-like component of sperm chromatin, and of protamine B (ProtB), which contributes to formation of condensed sperm chromatin, is regulated at three levels. Transcription of Mst77F is guided by a short, promoter-proximal region, while expression of the Mst77F protein is regulated at two levels, early by translational repression via sequences mainly in the 5′ part of the ORF and later by either protein stabilization or translational activation, dependent on sequences in the ORF. The protB gene is a direct target of tTAFs, with very short upstream regulatory regions of protB (−105 to +94 bp) sufficient for both cell-type-specific transcription and repression of translation in spermatocytes. In addition, efficient accumulation of the ProtB protein in late elongating spermatids depends on sequences in the ORF. We present evidence that spermatocytes provide the transacting mechanisms for translational repression of these mRNAs, while spermatids contain the machinery to activate or stabilize protamine accumulation for sperm chromatin components. Thus, the proper spatiotemporal expression pattern of major sperm chromatin components depends on cell-type-specific mechanisms of transcriptional and translational control.